Segmentasi Kemitraan B2B Pada PT Petir Indonesia Dengan Menggunakan Metode RFM Untuk Menganalisis Loyalitas dan Kemitraan - Harahap, Doni Magat; Octavianson, Dave Nathanael; Heikal, Jerry (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the segmentation and characteristics of PT Petir Indonesia's business partners using the Recency, Frequency, and Monetary (RFM) method to evaluate the effectiveness of partnership relationships in supporting operational efficiency and project sustainability. In this context, it is crucial for the company to have an effective evaluation mechanism to ensure that relationships with partners or vendors contribute to achieving the company's strategic objectives.Transaction data from the past year serves as the basis for analysis, covering contract transaction value (Monetary), the frequency of contracts awarded (Frequency), and the most recent collaboration period (Recency). Through this approach, business partners are classified into three main categories: loyal partners, potential partners, and non-loyal partners. The findings indicate that the RFM method can systematically categorize partners, providing strategic insights for PT Petir Indonesia.Loyal partners are identified as a group that should be prioritized for long-term relationship development, while potential partners require support to enhance their loyalty and performance. Non-loyal partners require further evaluation to determine the feasibility of continued collaboration. This study is expected to serve as a foundation for more effective decision-making in partnership management, thereby supporting the company's overall business sustainability.